Effects of Resistance Training With Constant, Inertial, and Combined Loads on Muscle Power and Strength Output - Đurić, Saša; Knezevic, Olivera M.; Sember, Vedrana; Cuk, Ivan; Nedeljkovic, Aleksandar; Pajek, Maja; Mirkov, Dragan M. (Frontiers in Physiology, 2021)
The aim of this study was to investigate the resistance-specific gains in muscle power and strength (1RM) following the training of maximum bench-press throws (BPT) against constant, inertial, and combined resistance. Forty-eight male participants (age 20.5 ± 2.0 years) were randomly assigned to the constant, inertial, combined resistance, or control group. Participants underwent 8 weeks of training of BPT against the loads that corresponded to the different effects of mass of 40 kg (∼50% of 1RM). The gains in average and maximum power, and 1RM were significant in all experimental groups (P < 0.01), but not in the control group (P > 0.1). Relative gains in the average (26.3 ± 9.8%) and maximum power (25.2 ± 9.8%) were larger than that in the 1RM (mean 7.2 ± 6.9%; both P < 0.001). The gains in the average (F4, 66 = 6.0; P < 0.01) and maximum power (F4, 66 = 4.7; P < 0.01) were higher when tested against the training-specific resistance than when tested against the remaining two resistance types. Differences in 1RM among experimental groups were not significant (P = 0.092). The most important and rather novel finding of the study is that the training against the weight and inertial resistance, and their combination results in resistance-specific gains in muscle power, although the overall gains muscle strength and power remain comparable across the training protocols.